Balancing act: the complex role of NK cells in immune regulation - Jiang, Hongwei; Jiang, Jingting (Frontiers in Immunology, 2023)
Natural killer (NK) cells, as fundamental components of innate immunity, can quickly react to abnormalities within the body. In-depth research has revealed that NK cells possess regulatory functions not only in innate immunity but also in adaptive immunity under various conditions. Multiple aspects of the adaptive immune process are regulated through NK cells. In our review, we have integrated multiple studies to illuminate the regulatory function of NK cells in regulating B cell and T cell responses during adaptive immune processes, focusing on aspects inculding viral infections and the tumor microenvironment (TME). These insights provide us with many new understandings on how NK cells regulate different phases of the adaptive immune response.